Дурацкая история: повести - Вильмонт Екатерина Николаевна (Лучшие детектива Е. Вильмонт для девочек, 2012)
Экземпляры: (20220214) / Инвентарный номер: 3958 / Цена: / Сис.шифр: 84Р6 / Авт.знак: В 46 / ББК: 84(2Рос=Рус)6